The Role of Shyness in the Adaptability of First-Year Students with Peer Attachment as a Moderator - Imam Dedikasi Malik Nur; Arief Rahman Nur Fadhilah; M. Allamal Badri; Prihastuti Prihastuti (Bisma The Journal of Counseling, 2026)
Many first-year students still experience difficulties adjusting to the academic, social, and emotional environment of college. Furthermore, personality factors such as shyness are thought to influence the success rate of new students' adjustment to the demands of campus life. This study aims to analyze the effect of shyness on first-year students’ self-adjustment ability as well as the moderating role of peer attachment. The research employed a cross-sectional design with a population of 100 freshmen in Surabaya. Data were collected through questionnaires consisting of shyness, peer attachment, and self-adjustment scales. Moderated regression analysis was used to examine the relationships among the variables. The results showed that shyness had a significant negative effect on freshmen’s self-adjustment ability (p < 0.001), while peer attachment did not moderate this relationship (p > 0.05). These findings indicate that students who experience shyness tend to face difficulties in adapting, whereas peer support alone is insufficient to reduce the negative impact of shyness. This study concludes that shyness greatly affects new student acclimation. Students with high shyness may struggle with academics, socializing, mood regulation, and campus activities. Therefore, social support and a positive campus environment are needed to help new students adapt better. This study suggests the need to place greater emphasis on the quality of social relationships and environmental support to improve freshmen’s adjustment.